Audit Effort on Tone Ambiguity in 10-K Filings - Kim, Martin M.; Belina, Hambisa (Journal of Accounting and Finance, 2023)
This study examines the association between ambiguous words (uncertain and weak modal words) in 10-K filings and audit fees. We find a positive association between ambiguous words in 10-K filings and audit fees. Results show that auditors put more time and effort into analyzing clients’ reports containing more ambiguous words. We conduct a propensity score matching technique to address potential endogeneity in client characteristics, which presents further empirical support for our main results. We re-estimate the main analysis for robustness tests by excluding firms with going concern opinions, firms audited by Big 4, and firms that report a net loss. We find the main results still hold in all robustness tests. The results of this study can be in the interest of multiple stakeholders, such as issuers, investors, auditors, and regulators, in that the 10-K report is mandatory, but the discretion of the management determines the degree of clarity of the text in the 10-K filings. Therefore, the interpretation and decisions of users of these ambiguous reports are non-trivial.